1906
DOI: 10.1113/jphysiol.1906.sp001148
|View full text |Cite
|
Sign up to set email alerts
|

On some physiological actions of ergot

Abstract: A PRELIMINARY note on the phenomena dealt with more completely in this paper was entitled, " The Physiological Action of Chrysotoxin'." Since the date of that publication further experiment has shown that the action is due to a principle, or combination of principles, which, by the aid of the physiological test, can be recognised in the various substances for which the title of "active principle" has been claimed, and indeed in all preparations of ergot possessing therapeutic activity. The active resin extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
236
0
26

Year Published

1931
1931
1985
1985

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 930 publications
(265 citation statements)
references
References 0 publications
3
236
0
26
Order By: Relevance
“…The exercise was terminated because of (16) The blood pressure response was (17) ST-T changes: (18) Arrhythmias: (19) …”
Section: Subject's Signature Datementioning
confidence: 99%
“…The exercise was terminated because of (16) The blood pressure response was (17) ST-T changes: (18) Arrhythmias: (19) …”
Section: Subject's Signature Datementioning
confidence: 99%
“…The ergotamine-resistant motor innervation of the mammalian myocardium has always been a puzzle to investigators attempting to differentiate adrenergic receptors pharmacologically (Dale, 1906;Lands, 1949).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The possible existence of a humoral receptor-modifying factor allows a reassessment of the receptor (Dale, 1906;Ahlquist, 1948) and the humoral theories (Cannon and Rosenblueth, 1933) of differential adrenergic responses. Either theory can explain direct adrenergic effects on various organs, but the humoral theory of Cannon and Rosenblueth has been largely abandoned because the postulated mediator + sympathin l or E complexes have not been identified.…”
Section: \mentioning
confidence: 99%
See 1 more Smart Citation
“…As early as 1906 Dale (1) reported that adrenaline causes relaxation of detrusor muscle and contraction of the vesical sphincter. However, the response of ureter to sympatho mimetic amines is indefinite; some experiments indicate that the motility and tone of the ureter are lessened (2) while in the rabbit Ahlquist (3) observed a stimulant effect of the amines on the ureter.…”
mentioning
confidence: 99%